Carotenoids in the treatment of age-related macular degeneration: a drug delivery system does matter - M.L. Maximov; Zh.G. Oganezova; I.D. Kanner; Voznesenskaya A.A (РМЖ "Клиническая офтальмология")
M.L. Maksimov1–3, J.G. Oganezova3,4, I.D. Kanner5, A.A. Voznesenskaya6 1Kazan State Medical Academy — Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 3Pirogov Russian National Research Medical University, Moscow, Russian Federation 4Research Center for Medical Genetics, Moscow, Russian Federation 5Lomonosov Moscow State University, Moscow, Russian Federation 6National Medical Research Center of Endocrinology, Moscow, Russian Federation Age-related macular degeneration (AMD) is one of the leading causes of low vision and blindness worldwide for people over age 60. By 2040, the number of people living with macular degeneration is expected to reach 288 million due to the exponential acceleration of population aging. A decline in visual functions caused by AMD has a significant economic impact in all countries. Besides aging, there are other multiple heterogenic risk factors associated with AMD: gender, environmental condition, lifestyle, genetic characteristics, chronic inflammatory processes in the human body, level of education, etc. It is important for the ophthalmologist to be aware of modifiable risk factors and thus to collect a comprehensive medical history, interact with patients using motivational interviewing and to involve promptly other healthcare specialists into the patient management strategy. Etiopathogenesis of AMD is still not entirely understood. However, it is known that the major pathways include age-related alterations of retinal pigment epithelium (RPE) cells, oxidative stress, dysregulated lipid metabolism, inflammation, hemodynamic changes, and neovascularization. Carotenoids lutein and zeaxanthin are natural compounds with a proven efficacy in reducing AMD progression, which have been demonstrated to act as medications for patients with early AMD stages. The micro-encapsulated formula offers such an advantage as gradual and controlled release of active substances. Keywords: age-related macular degeneration, risk factors, etiopathogenesis, carotenoids, lutein, zeaxanthin, microcapsules. For citation: Maksimov M.L., Oganezova J.G., Kanner I.D., Voznesenskaya A.A. Carotenoids in the treatment of age-related macular degeneration: a drug delivery system does matter. Russian Journal of Clinical Ophthalmology. 2023;23(1):60–65 (in Russ.). DOI: 10.32364/2311-7729-2023-23-1-60-65.